An Analytical Study of Language Styles in Different English Dialects - Afnan Musyaffa; Lusiana Suciati Dewi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This article aims to investigate language style variations within different dialects of the English language. Focusing on language elements such as vocabulary, syntax, and speech style, the research adopts an analytical approach to comprehend differences in language usage across several dialects. The research methodology involves the collection and analysis of data from representative text sources of each dialect. The findings highlight significant differences in language varieties, reflecting the cultural richness and historical background behind the development of these dialects. These results provide profound insights into the complexity of the English language through the lens of dialects, which can be valuable for cross-cultural understanding and the development of more effective communication strategies.